Keuangan Berbasis Digital dan Fintech: Penelitian - Takdirmin; Nurul Mukhlisah; Suratmi Dahlan; St. Nurasiah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The low level of financial inclusion in Indonesia, which is not comparable to the financial literacy of the community, is a major problem in the context of the digital transformation of the financial sector. This study aims to analyze the role of Financial Technology (Fintech) in expanding financial access, identifying its positive and negative impacts on society, and evaluating the effectiveness of the regulatory and educational approaches applied. This study uses a descriptive qualitative method with data collection techniques through literature studies, documentation, and indirect observation of Fintech usage trends. The results of the study show that the most widely used Fintech services are digital wallets (85%), followed by online loans (60%) and digital investment (40%), while insurtech and crowdfunding are still low in use. Although Fintech has increased financial access, weak literacy and supervision raise the risk of misuse and digital insecurity. In conclusion, the development of inclusive, safe, and sustainable Fintech requires synergy between technological innovation, consumer protection, and increasing public financial literacy.